Effect of bacterial monoassociation on brush-border enzyme activities in ex-germ-free piglets: comparison of commensal and pathogenic Escherichia coli strains - Kozakova, Hana; Kolinska, Jirina; Lojda, Zdenek; Rehakova, Zuzana; Sinkora, Jiri; Zakostelecka, Marie; Splichal, Igor; Tlaskalova-Hogenova, Helena (Microbes and infection, 2006)
This study was designed to investigate the effect of monoassociation of germ-free piglets with Escherichia coli strains on the development of intestinal brush-border enzyme activities. Piglets were delivered by hysterectomy, reared for seven days under germ-free conditions and fed milk formula diet. One group was maintained germ-free, the other four groups were monoassociated on day eight with one of four E. coli strains: non-pathogenic O86 or O83 and G58-1, or pathogenic 933D. The development of brush-border digestive enzyme functions in the small intestine was evaluated after 15 days. Germ-free controls exhibited slower developmental declines of lactase, gamma-glutamyltranspeptidase and alkaline phosphatase, and delayed increases of sucrase and glucoamylase compared to conventionally grown animals. Association of germ-free piglets with the non-pathogenic E. coli strains O86 and O83 resulted in increased enterocyte differentiation along the length of the small intestine, accompanied by declining activities of lactase, gamma-glutamyltranspeptidase and alkaline phosphatase, and elevated activities of maturational markers such as sucrase and glucoamylase. Maturational changes also occurred along the villus-crypt axis, as revealed by histochemical localization of aminopeptidase N on the villi tips in piglets colonized with E. coli O83. Interestingly, colonization with the pathogenic E. coli strain 933D stimulated changes in the main differentiation enzyme markers lactase, sucrase and glucoamylase to an extent comparable with those produced by the non-pathogenic and probiotic E. coli strains. In conclusion, germ-free piglets represent a valuable tool to study the consequences of colonization of the immature sterile gut with defined strains of bacteria.
Keywords: antigeny CD13; Animals; gnotobiologické modely; Glucan 1,4-alpha-Glucosidase; Lactase; Escherichia coli; Tumor Necrosis Factor-alpha; Intestine, Small; alkalická fosfatasa; prasata; Microvilli; Histocytochemistry; Sucrase; glukoamylasa; Germ-Free Life; TNF-alfa; laktasa; Swine; mikroklky; histocytochemie; sacharasa; Alkaline Phosphatase; gamma-Glutamyltransferase; zvířata; bakteriální adheze; gama-glutamyltransferasa; CD13 Antigens; Bacterial Adhesion; tenké střevo